Gas exchange of potted Tabebuia aurea plants under hydric stress - doi: 10.4025/actasciagron.v33i4.11254 (Acta Scientiarum. Agronomy, 2011)
To evaluate the effects of hydric stress on CO2 and H2O exchange, five-month-old Tabebuia aurea seedlings cultivated in planting bags were subjected to hydric stress by suppressing irrigation for 21 days. After 14 days without irrigation, the rates of transpiration, stomatal conductance and net photosynthesis in leaves were zero, while the hydric potential of leaves reached -2.4 MPa. After this point, daily irrigation was resumed, and the values of the measured variables recovered to initial levels after 96 hours (transpiration rate from 3.2 to 3.5 mmol m-2 s-1; stomatal conductance rate from 0.32 to 0.35 mol m-2 s-1 and photosynthesis rate from 8.0 to 9.8 µmol m-2 s-1). Likewise, hydric potential values were similar to those at the beginning of the experiment (-0.6 MPa). These results demonstrate that T. aurea has mechanisms to tolerate a period of hydric deficit, which may be considered ecologically relevant.